Patients' perceptions of the triage system in a primary healthcare facility, Cape Town, South Africa - Adeloye A. Adeniji; Bob Mash (AOSIS, 2016)
Background: In public healthcare facilities, where the patient numbers and the available resources are often disproportionate, triage is used to prioritise when patients are seen. Patients may not understand the triage process and have strong views on how to improve their experience. Aim: This study explored the views of patients who had undergone triage in the emergency centre of a primary care facility. Setting: Gugulethu Community Health Centre, Cape Town. Methods: A purposive sample consisted of five women (one coded green, three orange, one yellow) and four men (one coded green and three yellow). A semi-structured qualitative interview was conducted in either Xhosa or English and the transcripts analysed using the framework method. Results: All of the respondents complained of a lack of information and poor understanding of the triage process. Those coded green experienced the process as biased and unfair and reported that the triage nurse was rude and unprofessional. By contrast, those coded yellow or orange found the triage nurse to be helpful and professional. Most patients turned to support staff (e.g. security staff or cleaners) for assistance in dealing with the triage system. Most patients waited longer than the guidelines recommend and the green-coded patients complained about this issue. Conclusion: Patients did not have a good experience of the triage system. Managers of the triage system need to design better strategies to improve patient acceptance and share information. The important role of support staff needs to be recognised and strengthened. Keywords: emergency care; primary care; triage; patient satisfaction